Profils Des Femmes A Consommation Problematique De Drogues En Cote d’Ivoire - Guillaume, Dje Bi Tchan; Chaka, Coulibaly Onata (European Scientific Journal, ESJ, 2017)
Drug use is growing rapidly in Côte d'Ivoire, leading to serious adaptation difficulties and mental health problems. The present study aims at presenting the profile of women with drug use problem in Côte d'Ivoire. The participants, aged 14 to 67 years, were 83 patients of the Blue Cross of Côte d'Ivoire. Data related to drug use were obtained through urine tests (Rapitest) and semi-directive interviews with patients and their resource persons. The results indicate three profiles of women with problematic use. They also indicate that 4/5 of these women are poly-consumers. Considering these results, and given the growing interest of women in decision-making structures, it seems useful to reinforce measures to prevent and / or care for girls in drug problem.